Speaking the unspeakable : the ethics of dual relationships in counselling and psychotherapy - Gabriel, Lynne (Routledge, 2005)
"Speaking the Unspeakable provides an in-depth exploration of client-practitioner dual relationships, offering critical discussion and sustained narrative on thinking about, and being in, dual relationships."--Jacket